Plastic Design of Elements of Bolt and Pin Joints Subjected to Compressive Loads - Zowczak, W. (Engineering Transactions, 2015)
Two types of statically admissible stress fields for plastic design of are proposed. They are constructed by the method of characteristics (slip–lines), known from the theory of plastic flow. The structure of the fields is described and examples of possible applications are presented.